Implementation of Kurikulum Merdeka in Informatics subject at SMP Negeri 1 Katapang - Sandy Achmad Nugraha (Himpunan Pengembang Kurikulum Indonesia, 2026)
Curriculum transformation in Indonesia, particularly through the implementation of the Kurikulum Merdeka, responds to educational needs that must adapt to technological advancements and the demands of the digital era. This study aims to analyze the implementation of Kurikulum Merdeka in the Informatics subject at SMP Negeri 1 Katapang, focusing on curriculum adaptation, challenges, and the instructional strategies employed by teachers and students. A descriptive qualitative approach was adopted, utilizing in-depth interviews with the Informatics teacher and the vice-principal for curriculum affairs; the data were subsequently analyzed using the Miles and Huberman model to gain an empirical overview of the curriculum's implementation dynamics. The findings indicate that teachers successfully developed instructional innovations, such as Student-Centered Learning, Computer Science Unplugged, and the